2013
DOI: 10.1051/epjconf/20135209005
|View full text |Cite
|
Sign up to set email alerts
|

IceCube and ANTARES

Abstract: Abstract. IceCube and ANTARES are neutrino detectors sensitive to energies from 20 GeV up to PeV. Both detectors have been completed and take data. Several years of data have been already analysed including periods with the partly assembled detectors. The primary goal of these two neutrino telescopes is the observation of astrophysical sources of neutrinos. Results from searches for such neutrinos with different strategies will be presented as well as measurements of atmospheric neutrinos which are an irreduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Previous results are upper limits to the model in Ref. [131] from IceCube only [132] and with ANTARES data [133], which already indicated that the flux will be soon observed and that its contribution to the diffuse IceCube neutrino flux at > 60 TeV is < 10% [134]. As already noted in Sec.…”
Section: Teresa Montarulisupporting
confidence: 55%
“…Previous results are upper limits to the model in Ref. [131] from IceCube only [132] and with ANTARES data [133], which already indicated that the flux will be soon observed and that its contribution to the diffuse IceCube neutrino flux at > 60 TeV is < 10% [134]. As already noted in Sec.…”
Section: Teresa Montarulisupporting
confidence: 55%